A Modulated Helical Nanofilament Phase1. Issue 20 (19th April 2013) - Tsai, Ethan; Richardson, Jacqueline M.; Korblova, Eva; Nakata, Michi; Chen, Dong; Shen, Yongqiang; Shao, Renfan; Clark, Noel A.; Walba, David M.
<x xml:space="preserve">Abstract</x> A new liquid crystal phase, denoted modulated helical nanofilament (HNF(mod)), is formed from a very simple class of biphenyl carboxylates lacking the benzylidene aniline moieties typically found in HNF mesogens. The HNF(mod) phase represents a novel kind of nanoparticle possessing stacked aromatic rings, with potential applications in organic electronics.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>